Intrinsic Stress in ZrN Thin Films: Evaluation of Grain Boundary Contribution From in Situ Wafer Curvature and Ex Situ x-ray Diffraction Techniques - Abadias, Gregory; Koutsokeras, Loukas E. (My University, 2012)
Low-mobility materials, like transition metal nitrides, usually undergo large residual stress when sputter-deposited as thin films. While the origin of stress development has been an active area of research for high-mobility materials, atomistic processes are less understood for low-mobility systems. In the present work, the contribution of grain boundary to intrinsic stress in reactively magnetron-sputtered ZrN films is evaluated by combining in situ wafer curvature measurements, providing information on the overall biaxial stress, and ex situ x-ray diffraction, giving information on elastic strain (and related stress) inside crystallites. The thermal stress contribution was also determined from the in situ stress evolution during cooling down, after deposition was stopped. The stress data are correlated with variations in film microstructure and growth energetics, in the 0.13-0.42 Pa working pressure range investigated, and discussed based on existing stress models. At low pressure (high energetic bombardment conditions), a large compressive stress is observed due to atomic peening, which induces defects inside crystallites but also promotes incorporation of excess atoms in the grain boundary. Above 0.3-0.4 Pa, the adatom surface mobility is reduced, leading to the build-up of tensile stress resulting from attractive forces between under-dense neighbouring column boundary and possible void formation, while crystallites can still remain under compressive stress
Keywords: Grain boundaries; Thin films; Transition metals; Transition metal nitrides; Physics